Resisting attraction: Individual differences in executive control are associated with subject-verb agreement errors in production - Veenstra, Alma; Antoniou, Kyriakos; Katsos, Napoleon; Kissine, Mikhail (Journal of experimental psychology. Learning, memory, and cognition, 2018)
We propose that attraction errors in agreement production (e.g., the key to the cabinets are missing) are related to two components of executive control: working memory and inhibitory control. We tested 138 children aged 10 to 12, an age when children are expected to produce high rates of errors. To increase the potential of individual variation in executive control skills, participants came from monolingual, bilingual, and bidialectal language backgrounds. Attraction errors were elicited with a picture description task in Dutch and executive control was measured with a digit span task, Corsi blocks task, switching task, and attentional networks task. Overall, higher rates of attraction errors were negatively associated with higher verbal working memory and, independently, with higher inhibitory control. To our knowledge, this is the first demonstration of the role of both working memory and inhibitory control in attraction errors in production. Implications for memory- and grammar-based models are discussed. (PsycINFO Database Record